Socioeconomic status, remoteness and tracking of nutritional status from childhood to adulthood in an Australian Aboriginal Birth Cohort: the ABC study - Pauline Sjöholm; Katja Pahkala; Belinda Davison; Markus Juonala; Gurmeet Singh (NLM (Medline), 2022)
Objectives To determine prevalences of underweight and overweight as well as low and high waist-to-height ratio (WHtR) in three prospective follow-ups and to explore tracking of these measures of nutritional status from childhood to adolescence and adulthood. The influence of socioeconomic status, remoteness, maternal body mass index (BMI) and birth weight on weight status was assessed.
Design Longitudinal birth cohort study of Indigenous Australians.
Setting Data derived from three follow-ups of the Aboriginal Birth Cohort study with mean ages of 11.4, 18.2 and 25.4 years for the participants.
Participants Of the 686 Indigenous babies recruited to the study between 1987 and 1990, 315 had anthropometric measurements for all three follow-ups and were included in this study.
Primary and secondary outcome measures BMI categories (underweight, normal weight, overweight and obesity), WHtR categories (low and high), sex, areal socioeconomic disadvantage as defined by the Indigenous Relative Socioeconomic Outcomes index, urban/remote residence, maternal BMI and birth weight. Logistic regression was used to calculate ORs for belonging to a certain BMI category in adolescence and adulthood according to BMI category in childhood and adolescence.
Results Underweight was common (38% in childhood and 24% in adulthood) and the prevalence of overweight/obesity increased with age (12% in childhood and 35% in adulthood). Both extremes of weight status as well as low and high WHtR tracked from childhood to adulthood. Underweight was more common and overweight was less common in remote and more disadvantaged areas. Birth weight and maternal BMI were associated with later weight status. There were significant sex differences for prevalences and tracking of WHtR but not for BMI.
Conclusions Socioeconomic factors, remoteness and gender must be addressed when assessing nutrition-related issues in the Indigenous communities due to the variation in nutritional status and its behaviour over time within the Indigenous population.